Structural separation of data property rights based on data factor circulation value chain - Lihua HUANG; Wanli DU; Biyu WU (大数据)
Data property rights are of great significance in the data foundational institution system.Data property rights are structurally separated into three rights, namely, the right of data resource possessing, the right of data processing and the right of data product managing.Existing theories are not practice-oriented, and the responsive way of right-granting can hardly fix the market failures as well.Based on the data factor circulation practice, two typical logics of data factor circulation were proposed, namely, architecture logic and market logic.Based on market logic, the data factor circulation value chain model was constructed.The generated way of right-granting could provide an explanation of the structural separation of data property rights.